Illocutionary act in talk show of “The Tonight Show” by Jimmy Fallon - Giasi, Sri Meiyandi; Dako, Rahman Taufiqrianto; Danial, Haris (Priviet Social Sciences Journal, 2026)
Illocutionary act is one of the important parts of communication because it conveys the meaning of an utterance, so that it can be understood by the listener, and avoid misunderstanding in communication. This research aims to analyze the types of illocutionary acts used by Jimmy Fallon in his utterance on “The Tonight Show”. This research uses descriptive qualitative method, and for data collection uses note-taking method. The data in this study were analysed using Yule's (1996) theory that addressed to 5 types which are, declarative, representative, expressive, directive, and commissive. The results showed that Jimmy Fallon used 4 types of 5 types of illocutionary act in the seven The Tonight Show videos researched. The data found shows 31 sentences that are; 12 representative utterances, 11 expressive utterances, 7 directive utterances, and 1 commissive utterance. Meanwhile, the types of illocutionary act that is not found is declarative. Based on the results of the study, it could be concluded that the representative act is the most illocutionary act found in Jimmy Fallon's utterances. This study suggested to conduct a broader research on speech acts, not only in terms of illocutionary acts but also from other speech acts. This research contributed to influence how to interact, understand illocutionary acts in utterance, and build good social relationships with other people.